Experimental generation of complex noisy photonic entanglement - Dobek, K; Karpinski, M; Demkowicz-Dobrzanski, R; Banaszek, K; Horodecki, P (2013)
We present an experimental scheme based on spontaneous parametric down-conversion to produce multiple-photon pairs in maximally entangled polarization states using an arrangement of two type-I nonlinear crystals. By introducing correlated polarization noise in the paths of the generated photons we prepare mixed-entangled states whose properties illustrate fundamental results obtained recently in quantum information theory, in particular those concerning bound entanglement and privacy. © 2013 Astro Ltd.